Coffee to Go Marketing Mix (7P) Analysis to Improve Customer Satisfaction (Case Study Katuhu Coffee) - Muhammad Fauzan Abdurrahman; Arief Daryanto; Ani Nuraisyah (Business Review and Case Studies, 2021)
In the 4.0 era, coffee consumption during the 2016–2021 period is predicted to grow an average of 8.22 percent per year. Coffee milk is the best-selling product in the industry. Meanwhile, the development of technology and online transportation allows consumers to order food and beverages from home. This brings the concept of a new coffee shop business model; it is called Coffee to Go. There are so many Coffee to Go in Bogor City, which makes the industry more competitive. This study aims to know Katuhu Coffee's consumer target's characteristics and consumer behavior, customer satisfaction index of Katuhu, importance and performance index of Katuhu Coffee's marketing mix, and formulate marketing strategies for Katuhu Coffee. This research uses the importance-performance analysis (IPA) and customer satisfaction index (CSI) method. The CSI of Katuhu Coffee is 77.2 percent with menu variants, convenient place, doing endorsement, and doing promos in online stores are the attributes need to be fixed. The resulting strategy based on priority includes (1) Innovative menus and product size for coffee and non-coffee menus; (2) Increasing online store promos; (3) Increasing doing endorsement and Instagram ads; (4) Increasing convenience in offline store services; and (5) Expanding Katuhu Coffee sales channel. Keywords: coffee in era 4.0, coffee to go, coffee milk, consumer satisfaction, CSI, IPA